Who is responsible for what? On the governance relationship between ministry and agencies in Austrian and Norwegian higher education. Issue 12 (2nd December 2021) - Friedrich, Philipp Emanuel
ABSTRACT: This article addresses the governance relationship between the ministry responsible for higher education and the sector agencies against the backdrop of comprehensive sector reforms. The relationship is examined based on autonomy and capacity, which are argued to be decisive in negotiating areas of responsibility. The Austrian and Norwegian ministries responsible for higher education and their interplay with two subordinate agencies exemplify this negotiation process empirically. The findings, based on data derived from organizational figures, policy documents, law texts, and interviews with politicians, bureaucrats, and academics, show that the initial years of a changed modus operandi were characterized by uncertainty about the roles and expectations of the organizations involved. The more time passed the more consolidated and aligned the new governance practices became, although this consolidation and alignment depended on various autonomy and capacity determinants, which played out differently in both national contexts.